Peran PRABU dalam Meningkatkan Kesiapan Akademik bagi Mahasiswa Baru STAB Kertarajasa Batu - Dina Yana Dewi; Sentot; Aryanto Firnadi (STAB Kertarajasa, 2026)
The purpose of this study is to determine and describe the role of new student training and orientation (PRABU) in improving academic readiness for new students. This study uses qualitative with a descriptive analysis approach. This study uses data collection techniques through interviews, observations and documentation. Data analysis uses three stages, namely data condensation, data presentation and drawing conclusions and verification. The data sources in this study were obtained from primary data, namely the results of interviews with new students, lecturers involved, and the PRABU Kertarajasa Batu committee. While secondary data from journals, PRABU documents, books, and PRABU guidelines. The results of this study indicate that PRABU plays a significant role in the academic readiness of new STAB Kertarajasa students. This can be seen when new students fol low class learning well, complete assignments given by lecturers on time, and can adapt to the campus environment, friends and lecturers. However, academic readiness also depends on each individual and cannot be generalized.